Supplier performance in the public healthcare: internal social capital, logistics capabilities and supply chain risk management capabilities as antecedents in a developing economy - Tukamuhabwa, Benjamin; Mutebi, Henry; Isabirye, Daniel (Journal of Business and Socio-economic Development, 2021)
Purpose – The purpose of this paper is twofold. First, it intends to explore the link between internal social capital, logistics capabilities, supply chain risk management (SCRM) capabilities and supplier performance. Second, the mediating effect of logistics capabilities between internal social capital and SCRM capabilities, and that of SCRM capabilities between logistics capabilities and supplier performance are also examined. Design/methodology/approach – A theoretical model developed from the extant literature was empirically validated through a cross-sectional survey of 122 respondents in 52 public healthcare facilities in Uganda. The data were analysed using partial least square structural equation modeling (PLS-SEM). Findings – The study found that internal social capital and SCRM capabilities are significant predictors of supplier performance. Internal social capital is positively and significantly related to logistics capabilities, and logistics capabilities are positively and significantly related to SCRM capabilities. The authors also found nonsignificant relationships between internal social capital and SCRM capabilities, and between logistics capabilities and supplier performance. Furthermore, it was revealed that logistics capabilities play a partial mediating role in the relationship between internal social capital and SCRM capabilities, while SCRM capabilities fully mediate between logistics capabilities and supplier performance. Originality/value – Further to providing empirical evidence of the antecedents of supplier performance in the public healthcare in a developing economy, which has been evidently scant, this study provides initial empirical evidence of the mediating role of logistics capabilities in the relationship between internal social capital and SCRM capabilities and that of SCRM capabilities in the relationship between logistics capabilities and supplier performance. This is important for understanding the mechanism through which supplier performance can be enhanced.
Keywords: Supplier performance; Logistics capabilities; Internal social capital; Supply chain risk management capabilities; Healthcare